Telemedicine in Otolaryngology: A Systematic Review of Image Quality, Diagnostic Concordance, and Patient and Provider Satisfaction. (February 2021) - Ning, Anne Y.; Cabrera, Claudia I.; D'Anza, Brian
Objectives: Telemedicine allows for the remote delivery of patient care and has been found to have a wide range of uses in otolaryngology. In order to achieve best practices in telemedicine, a platform must be effective and both patients and providers must be satisfied with the use of technology. As telemedicine becomes more widely used in otolaryngology clinics, particularly in the face of the current COVID-19 pandemic, it is important to assess its applicability in this field. The goal of this study was to evaluate existing literature on telemedicine and assess overall image quality, diagnostic concordance, and patient and provider satisfaction with telemedicine technologies. Methods: A systematic review was conducted on PubMed and MEDLINE according to the PRISMA 2009 guidelines for articles from 1982 to 2019 relating to telemedicine in otolaryngology. English language studies with primary or secondary endpoints pertaining to image quality, diagnostic concordance, or patient or provider satisfaction were included. Descriptive studies, editorials, and literature reviews were excluded. Results: A total of 32 studies were included in our review. Studies assessing imaging quality and diagnostic concordance reported adequate results but with some heterogeneity. Patient and provider satisfaction were consistently high. Conclusions: The literature supports telemedicine delivery of otorhinolaryngologic care as having achieved high rates of patient and provider satisfaction with adequate image quality and heterogeneity in diagnostic concordance. Variability in diagnostic accuracy was reported, but appears improved given proper clinical context. More standardized studies are needed specific to telemedicine in the field of otolaryngology.